Highlighting the clinical need for diagnosing Mycoplasma genitalium infection. (June 2018) - Ison, Catherine A; Fifer, Helen; Gwynn, Simon; Horner, Paddy; Muir, Peter; Nicholls, Jane; Radcliffe, Keith; Ross, Jonathan; Taylor-Robinson, David; White, John
Despite Mycoplasma genitalium (MG) being increasingly recognised as a genital pathogen in men and women, awareness and utility of commercially available MG-testing has been low. The opinion of UK sexual health clinicians and allied professionals was sought on how MG-testing should be used. Thirty-two consensus statements were developed by an expert group and circulated to clinicians and laboratory staff, who were asked to evaluate their level of agreement with each statement; 75% agreement was set as the threshold for defining consensus for each statement. A modified Delphi approach was used and high levels of agreement obviated the need to test the original statement set further. Of 201 individuals who received questionnaires, 60 responded, most (48) being sexual health consultants, more than 10% of the total in the UK. Twenty-seven (84.4%) of the statements exceeded the 75% threshold. Respondents strongly supported MG-testing of patients with urethritis, pelvic inflammatory disease or unexplained persistent vaginal discharge, or post-coital bleeding. Fewer favoured testing patients with proctitis and support was divided for routinely testing Chlamydia-positive patients. Testing of current sexual contacts of MG-positive patients was supported, as was a test of cure for MG-positive patients, although agreement fell below the 75% threshold. Respondents agreed that all consultant- or specialist-led services should have access to testing for MG (98.3%). There was strong agreement for having MG-testing available for specific patient groups, which may reflect concern over antibiotic resistance and the desire to comply with clinical guidelines that recommend MG-testing in sexual health clinic settings.